Electrical and electronics science laboratory experiments - Singh, Yaduvir (Alpha Science Internationl Ltd., 2012)
Electrical and electronics science starts with an introduction and details supply systems, sinusoidal steady state response of circuits, magnetic circuits, single phase transformers, rotating electrical machines and electronic devices and goes on to explain the theoretical and practical aspects of Kirchoffs laws, various network theorems, dynamical behavior of A.C. series a parallmel circuits, phenomenon of resonant circuits, theory and practice approaches for measurement of power in three phase circuits, reactance calculation of variable reactance choke coil. The book also discusses various starting methods of DC motor, three phase induction motor and single phase induction motors, experiments on identification of devices, study of V-I characteristics of P-N diode, Zener diode and BJT as amplifier. Uses of diode as half wave and full wave rectifier have also been included as separate experiments. It will serve as both a textbook for undergraduate students and as a valuable source of information for the working professionals in this area of engineering and technology